Prevalence and determinants of mother and newborn skin-to-skin contact in Ghana - Richard Gyan Aboagye; Khadijat Adeleye; Bright Opoku Ahinkorah (PLoS ONE, 2025)
Background Despite the well-established role of skin-to-skin contact in reducing neonatal mortality, its implementation varies significantly across geographical regions, particularly in sub-Saharan Africa. Therefore, we estimated the prevalence of mother and newborn skin-to-skin contact at birth and investigated the factors associated with its practice in Ghana. Methods We used data from the 2022 Ghana Demographic and Health Survey. The analysis included 3833 mother-child pairs. Data was analysed using Stata 17.0, with percentages and confidence intervals (CI) used to present the prevalence of mother and newborn skin-to-skin contact. We employed multilevel binary logistic regression models to examine factors associated with the practice of mother and newborn skin-to-skin contact. Results Overall, 67.2% [64.9 - 69.4] of mothers practised skin-to-skin contact. Delivery by caesarean section was associated with a decreased likelihood of mother and newborn skin-to-skin contact (adjusted odds ratio [aOR] = 0.04; 95% CI: 0.02, 0.06). Higher birth order (fifth or more) (aOR = 2.34, 95%CI: 1.13, 4.84) was significantly associated with increased odds of skin-to-skin contact. Women who had eight or more antenatal care visits were more likely to engage in skin-to-skin contact (aOR = 1.82; 95% CI: 1.04–3.21) than those with fewer than four visits. Women who delivered in a healthcare facility were more likely to practise skin-to-skin contact (aOR = 30.67; 95% CI: 18.93, 49.70) than those who delivered at home. Compared to women in the Western region, those in the Eastern (aOR = 2.85, 95%CI: 1.21, 6.73), Western North (aOR = 3.87, 95%CI: 1.60, 9.37), Ahafo (aOR = 3.09, 95%CI: 1.19, 8.02), North East (aOR = 4.44, 95%CI: 1.88, 10.50), Upper East (aOR = 3.67, 95%CI: 1.45, 9.31), and Upper West regions (aOR = 6.13, 95%CI: 2.33, 16.16) were more likely to practise skin-to-skin contact. Conclusion Our study has shown moderate mother and newborn skin-to-skin contact practise in Ghana, with significant regional variations. Going forward, any initiatives by the Ghana Health Service, the Ministry of Health, or other organisations focused on maternal and neonatal health must consider the geographical context of their efforts and programme implementation. Enhancing skin-to-skin contact requires increased advocacy and health education during antenatal care sessions, alongside higher attendance at such visits. Additionally, advocating for hospital births and reducing the number of home births is likely to boost skin-to-skin contact practices in Ghana.